Using Adobe Animated CC in Designing Interactive Multimedia Based on Cognitive Conflict on Parabolic Motion Materials - Prima Lestari Atmam; Fatni Mufit (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
In reality, most students still do not understand the concepts that have been taught, giving rise to misconceptions. One solution to overcome this problem is to design interactive multimedia based on cognitive conflict. The purpose of this study is to describe the characteristics and validity of interactive multimedia based on cognitive conflict. This type of research is development research using the Plomp development model. The research is limited to two stages, namely the preliminary research stage and the prototyping phase at the validity test stage by experts. The data collection instruments in this study were teacher questionnaire sheets, journal analysis sheets, self-evaluation sheets, and validity test sheets. The data analysis technique used the percentage technique and the V Aiken formula. Based on the preliminary research, the problem of understanding students' concepts was low, the learning model used was still teacher-centered, and interactive multimedia was not yet available. In the development or prototyping phase, interactive multimedia has been designed with the following characteristics: Using Adobe Animated CC, interactive multimedia is based on four syntaxes of cognitive conflict learning models. The results of self-evaluation were obtained with very good criteria. The validity test yielded an average of 0.75 with a valid category. So it can be concluded that interactive multimedia based on cognitive conflict in the parabolic motion material has been valid in terms of material substance, learning design, visual communication display, and software utilization.